A rare case of Ganglioneuroblastoma Encapsulated in Pheochromocytoma - Sousa, Nathália Vieira; Marques de Oliveira, Luísa Coelho; Cortez, Paulo José Oliveira; Valenti, Vitor Engrácia; Garner, David Mathew; Irulegui, Roseane de Souza Candido; Moreira, Dalmo Antônio Ribeiro (Acta medica (Hradec Kralove), 2016)
Pheochromocytoma and Ganglioneuroblastoma are separate diseases and a rare combination in which the diagnosis can only be confirmed by pathological examination after tumor excision. We reported here a case of ganglioneuroblastoma encapsulated in pheochromocytoma. The patient is a woman, 73 years old, hypertensive, with hypothyroidism, associated for 15 years with hypercholesterolemia and hypertriglyceridemia, which had frequent complaints of low back pain. She underwent magnetic resonance and the findings were consistent with the diagnosis of pheochromocytoma. After surgery, anatomic, pathologic and immunohistochemistry analysis confirmed the diagnosis of pheochromocytoma composed by small ganglioneuroblastoma representation with the identification of small focus of infiltration of the adrenal capsule and adipose tissue by pheochromocytoma. This rare association can instigate the discussion of methods of diagnosis, more effective and more appropriate treatments for each patient.
Keywords: ganglioneuroblastom; Magnetic Resonance Imaging; diferenciální diagnóza; Female; invazivní růst nádoru; ženské pohlaví; 3-Iodobenzylguanidine; 3-jodobenzylguanidin; vzácné nemoci; lidé; Pheochromocytoma; radioisotopová scintigrafie; nadledviny; magnetická rezonanční tomografie; nádory nadledvin; Catecholamines; Rare Diseases; Diagnosis, Differential; Radionuclide Imaging; Adrenal Gland Neoplasms; Neoplasms, Multiple Primary; feochromocytom; Aged; Adrenal Glands; mnohočetné primární nádory; Abdominal Neoplasms; senioři; Neoplasm Invasiveness; Ganglioneuroblastoma; katecholaminy; Humans